iPad Usage Design As Alternative Media In Medical Informatics Activities - Budi Berlinton Sitorus (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
In early 2010, a touch screen device, iPad,  was launched along with offers of various features provided. Tablet computer with its thinner shape and lighter tends to replace role either laptop or personal computer (PC). Medical informatics is a field that involves information science, computer science and health care. One of devices commonly used is laptop. According to the research conducted, a design of  iPad usage as alternative media in medical informatics activity was created through its features. This design was expected to make iPad be useful in medical informatics activities and create them to be more effective. Keywords: iPad, medical informatics, touch screen